The labour market effects of the Polish educational reform of 1999 - Luca Flóra Drucker; Dániel Horn; Maciej Jakubowski (Journal for Labour Market Research, 2022)
We estimate the effect of the 1999 education reform in Poland on employment and earnings. The 1999 education reform in Poland replaced the previous 8~years of general and 3/4/5~years of tracked secondary education with 9~years of general and 3/3/4~years of tracked upper-secondary education. The reform also introduced new curricula, national examinations, teacher standards, and a transparent financing scheme. Our identification strategy relies on a difference-in-differences approach using a quasi-panel of pooled year-of-survey and age-of-respondent observations from the Polish sample of the EU-SILC database. The results indicate that the reform has increased employment probability (by around 3 percentage points) and earnings (by around 4%).
Keywords: I21; I24; I26; J24; 330; Detracking; Difference-in-differences; Education reform; Labour market; Poland; Returns to education